The Effectiveness of Sensory-Motor Integration on Clumsiness in Children with Nonverbal Learning Disabilities - Saeid Sadeghi; Forogh Mohammadian; Hamidreza Pouretemad; Hamidreza Hasanabadi (مجله پژوهش در علوم توانبخشی, 2017)
Introduction: One of the most important problems of children with nonverbal learning disabilities is clumsiness and poor coordination. This issue prevents children’s academic achievement and socio-emotional development. This study aimed to evaluate the effectiveness of sensory-motor integration on clumsiness in children with nonverbal learning disabilities.